Produção, circulação e mediação literária juvenil: afinal, o que leem os jovens do século XXI? - Macêdo, Jhennefer Alves (2023)
The present research aims to bring up problematizations concerning the circulation and mediation of literary works in Elementary School – Final Years, bearing in mind that, when conducting interviews, both non-directive and through questionnaires, with students of the relevant educational level, coming from public and private teaching networks in the city of João Pessoa-PB, we visualize a considerable gap between teachers, students and literary readings, since they are absent from the classrooms (1) academically legitimized production, that is, the works that receive the seals of highly recommended for young people by national awards, such as those granted by JABUTI and FNLIJ – promoting an almost total lack of knowledge about these selections and the works that are nominated, those that should be brought, mainly, by educators to the classroom, as well as (2) the nominations made by the new digital literary curators called booktubers, and which, recurrently, are seen in the hands of adolescents at times opposite to those of classes, but which are usually classified as second-hand literature by many education professionals. Thus, based on these mismatches of voices and readings, we perceive a crisis in reader formation in the classroom, which sometimes happens due to the absence of books, the result of the problem of non-circulation and lack of knowledge about the productions, sometimes due to the non-prioritization of literary construction, during the training process, which should be based on the presentation of works selected by literary critics, but also on the insertion of productions that are read by young people, thus promoting literary meetings and the formation of plural readers. Therefore, considering these findings, in order to contribute to filling these gaps, especially according to mediation, we propose a research, with a quantitative and qualitative approach, which, beyond investigating, through approximations with the subjects involved in this scenario, that is, teachers, students, and literary curators, the motivations that are contributing to this removal of literary works from the school space, also aims, through the realization of literary reading circles, with students from two primary education schools, from public and private networks, to develop an intervention proposal, aiming to analyze the receptions, by readers, about these works, whether awarded by the academic field or best-sellers. As a result of this study, we evidenced that, by enlarging the horizons of literary works, whether in the process of selection, access, and execution of the reading and analysis process in the classroom, expands the reading perspectives of our students and, consequently, our perspectives as mediators, leading to a critical and pluralized reading formation. For the development of the discussions proposed here, in theoretical and practical scopes, we got anchored in the studies already developed by Chartier (1998); Zilberman (1993); Abreu (2006); Groppo (2000); Catani (2008); Cardona (2006); Bajour (2012); Oliveira (2013); Cosson (2014); Souza (2019); Colomer (2017); Santos (2018), among others.